The stiff upper LIP: investigating the High Arctic Large Igneous Province. (12th May 2016) - Deegan, F.M.; Troll, V.R.; Bédard, J.H.; Evenchick, C.A.; Dewing, K.; Grasby, S.; Geiger, H.; Freda, C.; Misiti, V.; Mollo, S.
Abstract : The Canadian Arctic Islands expose a complex network of dykes and sills that belong to the High Arctic Large Igneous Province (HALIP), which intruded volatile‐rich sedimentary rocks of the Sverdrup Basin (shale, limestone, sandstone and evaporite) some 130 to 120 million years ago. There is thus great potential in studying the HALIP to learn how volatile‐rich sedimentary rocks respond to magmatic heating events during LIP emplacement. The HALIP remains, however, one of the least well known LIPs on the planet due to its remote location, short field season, and harsh climate. A Canadian–Swedish team of geologists set out in summer 2015 to further explore HALIP sills and their sedimentary host rocks, including the sampling of igneous and meta‐sedimentary rocks for subsequent geochemical analysis, and high pressure‐temperature petrological experiments to help define the actual processes and time‐scales of magma–sediment interaction. The research results will advance our understanding of how climate‐active volatiles such as CO2, SO2 and CH4 are mobilised during the magma–sediment interaction related to LIP events, a process which is hypothesised to have drastically affected Earth's carbon and sulphur cycles. In addition, assimilation of sulphate evaporites, for example, is anticipated to trigger sulphide immiscibility in the magma bodies and in so doing could promote the formation of Ni‐PGE ore bodies. Here we document the joys and challenges of 'frontier arctic fieldwork' and discuss some of our initial observations from the High Arctic Large Igneous Province.